(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Addison disease is disorder of primary adrenocortical insufficiency that results from dysfunction or destruction of the adrenal gland. Clinical manifestations are usually non-specific and subtle leading to delay in diagnosis and associated high mortality and morbidity. The objective of this case report is to describe an acute emergency presentation of a 6 years old child of Addison s disease. As the differential diagnoses of such presentation may not initially include Addison , s disease, this case report is expected to create necessary awareness among the treating physicians. Case Presentation: We report a case of Addison Disease in a 6 years old boy who presented atypically with fever and CNS manifestations. Careful physical examination revealed blackening hyperpigmentation of the skin of the child who had circulatory collapse as well. Clinical suspicion of Addison disease raised and we investigated promptly, started specific treatment soon and the boy was saved. We could aware the parents about the life-long precaution to be undertaken for their child. We do emphasize on careful history taking, thorough physical examination and focused laboratory investigations to avoid missed or delayed diagnosis of this uncommon but fatal endocrine disorder. Conclusion: High index of clinical suspicion is needed to diagnose Addison disease with unusual presentation specially in children. Often the condition may be mimicked to other closely related differentials that the physicians should be aware of. JCMCTA 2023 ; 34 (2) : 157-160